2-Hydroxychalcone as a Potent Compound and Photosensitizer Against Dermatophyte Biofilms - Bila, Níura Madalena [UNESP]; Costa-Orlandi, Caroline Barcelos [UNESP]; Vaso, Carolina Orlando [UNESP]; Bonatti, Jean Lucas Carvalho [UNESP]; de Assis, Letícia Ribeiro [UNESP]; Regasini, Luís Octavio [UNESP]; Fontana, Carla Raquel [UNESP]; Fusco-Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Frontiers, 2021)
Dermatophytes, fungi that cause dermatophytosis, can invade keratinized tissues in humans and animals. The biofilm-forming ability of these fungi was described recently, and it may be correlated with the long treatment period and common recurrences of this mycosis. In this study, we evaluated the anti-dermatophytic and anti-biofilm activity of 2-hydroxychalcone (2-chalcone) in the dark and photodynamic therapy (PDT)-mediated and to determine its mechanism of action. Trichophyton rubrum and Trichophyton mentagrophytes strains were used in the study. The antifungal susceptibility test of planktonic cells, early-stage biofilms, and mature biofilms were performed using colorimetric methods. Topographies were visualized by scanning electron microscopy (SEM). Human skin keratinocyte (HaCat) monolayers were also used in the cytotoxicity assays. The mechanisms of action of 2-chalcone in the dark and under photoexcitation were investigated using confocal microscopy and the quantification of ergosterol, reactive oxygen species (ROS), and death induction by apoptosis/necrosis. All strains, in the planktonic form, were inhibited after treatment with 2-chalcone (minimum inhibitory concentration (MIC) = 7.8-15.6 mg/L), terbinafine (TRB) (MIC = 0.008–0.03 mg/L), and fluconazole (FLZ) (1–512 mg/L). Early-stage biofilm and mature biofilms were inhibited by 2-chalcone at concentrations of 15.6 mg/L and 31.2 mg/L in all tested strains. However, mature biofilms were resistant to all the antifungal drugs tested. When planktonic cells and biofilms (early-stage and mature) were treated with 2-chalcone-mediated PDT, the inhibitory concentrations were reduced by four times (2–7.8 mg/L). SEM images of biofilms treated with 2-chalcone showed cell wall collapse, resulting from a probable extravasation of cytoplasmic content. The toxicity of 2-chalcone in HaCat cells showed higher IC50 values in the dark than under photoexcitation. Further, 2-chalcone targets ergosterol in the cell and promotes the generation of ROS, resulting in cell death by apoptosis and necrosis. Overall, 2-chalcone-mediated PDT is a promising and safe drug candidate against dermatophytes, particularly in anti-biofilm treatment.
Keywords: 2-chalcone; biofilms; dermatophytes; mechanism of action; photodynamic therapy; T. mentagrophytes; Trichophyton rubrum